Gender dan Demokrasi dalam Pemilihan Kepala Daerah Kabupaten Tanah Datar Tahun 2020 - Luthfi Azura, Danisa; Adi Putri, Indah (Universitas Indo Global Mandiri, 2024)
This research analyzes the right of women to be elected in the election. However, the regional election in Tanah Datar Regency has its own challenges. Although Minangkabau culture adheres to a matrilineal system and has indigenous institutions such as Bundo Kanduang that give women an important role in maintaining cultural traditions and values, this does not automatically support women's involvement in politics. Based on these problems, researchers want to analyze these factors using the theory of Affirmative Action and the concept of the challenge of women Regional Head candidates in the regional elections. This study uses descriptive qualitative methods. The results of this study indicate that there are several challenges for Women Regional Head candidates in the 2020 regional elections in Tanah Datar Regency, socio-cultural barriers and economic barriers. Socio-cultural barriers in the nomination of women as candidates for regional heads is the public's view of women who become regional heads in Minangkabau. Patriarchal views in Tanah Datar where most people consider that men are more appropriate to lead than women, this is always associated with religion where the majority of West Sumatran society is Muslim. Economic barriers, insufficient Financial for women when nominating to be regional heads in flat lands that do not have financial power, have deficiencies in terms of social and economic power, it is increasingly difficult to enter the political sphere which is dominated by men, which is a challenge for women in running for political participation.